2020
DOI: 10.1039/d0ce00173b
|View full text |Cite
|
Sign up to set email alerts
|

Doping of metal-free molecular perovskite with hexamethylenetetramine to create non-centrosymmetric defects

Abstract: The metal-free perovskite (dabcoH22+)(NH4)Br (d-Br) (dabco: 1,4-diazabicyclo[2.2.2]octane) was doped with non-centrosymmetric hexamethylenetetramine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Ionic diffusion and partial ionic substitution might occur at several molecule layer levels between HMFE and perovskite.I th as been reported that al ittle bit of doping can change macroscopic behaviors. [21] This strong PL suggests that HMFE with unique chemical structure ( Figure S1) can effectively passivate the parasitic defects from perovskite through cation exchange and filling of iodide vacancies,w hich matches well with previous reports. [15,22] Time-resolved PL measurements also support the PL results (Figure 3b).…”
Section: Methodssupporting
confidence: 90%
“…Ionic diffusion and partial ionic substitution might occur at several molecule layer levels between HMFE and perovskite.I th as been reported that al ittle bit of doping can change macroscopic behaviors. [21] This strong PL suggests that HMFE with unique chemical structure ( Figure S1) can effectively passivate the parasitic defects from perovskite through cation exchange and filling of iodide vacancies,w hich matches well with previous reports. [15,22] Time-resolved PL measurements also support the PL results (Figure 3b).…”
Section: Methodssupporting
confidence: 90%
“…Ionic diffusion and partial ionic substitution might occur at several molecule layer levels between HMFE and perovskite. It has been reported that a little bit of doping can change macroscopic behaviors [21] . This strong PL suggests that HMFE with unique chemical structure (Figure S1) can effectively passivate the parasitic defects from perovskite through cation exchange and filling of iodide vacancies, which matches well with previous reports [15, 22] .…”
Section: Resultssupporting
confidence: 89%
“…B-Site is NH 4 + , H 3 O + , or alkali metal ion, and X site is a halide and molecular ions such as BF 4 − . [77][78][79][80][81][82][83][84][85] The size evolutions from inorganic perovskite to molecular perovskite via organic-inorganic perovskite are summarised in Table 1. B-Site ions of the molecular perovskite are more friendly to both human health and the earth environment.…”
Section: Solid Solution Of Molecular Perovskite Crystalsmentioning
confidence: 99%
“…84 Recently, we reported a solid solution for the metal-free molecular perovskite by mixing the A-site cations with centrosymmetric dabco and non-centrosymmetric hmta. 85 Both molecules are doubly protonated on N atoms, having molecules with D 3h (dabcoH 2 2+ ) and C 2v (hmtaH 2 2+ ) symmetry. Both cation form a perovskite-type structure (dabcoH 2 )(NH 4 )Br 3 (d-Br) 78 and (hmtaH 2 )(NH 4 )Br 3 (h-Br) (Fig.…”
Section: Solid Solution Of Molecular Perovskite Crystalsmentioning
confidence: 99%
See 1 more Smart Citation